The Supreme Court as the Guardian of Legality: The Coherence of Judicial Review of Electoral and Presidential Regulations - Irmanjaya Thaher; Annisa Fitria; M. Abyan Mufid (Hakamain: Journal of Sharia and Law Studies, 2024)
This study examines the Supreme Court’s role as the guardian of legality by evaluating the coherence of judicial review concerning electoral regulations and presidential regulations within Indonesia’s constitutional system. The research focuses on whether the Supreme Court has consistently applied legal principles in reviewing subordinate legislation to ensure conformity with statutory norms, constitutional values, and the rule of law. This study employs a normative legal research method using statutory, conceptual, and case approaches. Primary legal materials consist of the 1945 Constitution, legislation governing judicial power and lawmaking, Supreme Court decisions, Constitutional Court jurisprudence, and scholarly literature on judicial review and constitutional governance. The findings reveal that although the Supreme Court exercises constitutional authority to review regulations below statutes, inconsistencies remain in judicial interpretation of electoral regulations and presidential regulations, particularly where administrative discretion intersects with democratic governance and constitutional rights. Variations in legal reasoning have contributed to uncertainty regarding the hierarchy of legislation and the uniform application of legal principles. The study further finds that limited harmonization between the Supreme Court and the Constitutional Court has weakened the coherence of judicial review and occasionally produced conflicting legal interpretations. To address these challenges, the research argues for the development of consistent interpretative standards, stronger institutional coordination, and greater transparency in judicial reasoning. Harmonizing review procedures and reinforcing the Supreme Court’s constitutional function would enhance legal certainty, strengthen democratic accountability, and preserve the supremacy of the Constitution. Ultimately, coherent judicial review is indispensable for ensuring that electoral regulations and presidential regulations remain consistent with statutory authority, constitutional principles, and the fundamental requirements of a democratic state governed by the rule of law.